2009
DOI: 10.1172/jci38003
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctions of neuronal and glial intermediate filaments in disease

Abstract: Intermediate filaments (IFs) are abundant structures found in most eukaryotic cells, including those in the nervous system. In the CNS, the primary components of neuronal IFs are α-internexin and the neurofilament triplet proteins. In the peripheral nervous system, a fifth neuronal IF protein known as peripherin is also present. IFs in astrocytes are primarily composed of glial fibrillary acidic protein (GFAP), although vimentin is also expressed in immature astrocytes and some mature astrocytes. In this Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 129 publications
1
100
0
Order By: Relevance
“…In fact, the striking circular filament phenotype that we observe with the Y242D GFAP mutant is somewhat reminiscent of what has previously been shown with an R239C GFAP mutant, which also had decreased solubility (44). Furthermore, a characteristic feature of astrocytes in Alexander disease is the presence of GFAP aggregates called Rosenthal fibers (34). Whether site-specific GFAP tyrosine phosphorylation controls Rosenthal fiber formation and contributes to the pathogenesis of Alexander disease remains to be determined.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In fact, the striking circular filament phenotype that we observe with the Y242D GFAP mutant is somewhat reminiscent of what has previously been shown with an R239C GFAP mutant, which also had decreased solubility (44). Furthermore, a characteristic feature of astrocytes in Alexander disease is the presence of GFAP aggregates called Rosenthal fibers (34). Whether site-specific GFAP tyrosine phosphorylation controls Rosenthal fiber formation and contributes to the pathogenesis of Alexander disease remains to be determined.…”
Section: Discussionsupporting
confidence: 77%
“…3A). Importantly, the paralogous residue in GFAP (Tyr-242) is mutated (Y242D) in Alexander disease (33), an early-onset neurodegenerative disease that is associated with seizures, developmental delays, loss of psychomotor function, and a life expectancy of 5-10 years (34,35). Because Alexander disease Tyr-242 mutation in GFAP is also to a negatively charged aspartic acid residue, we probed whether this mutation paralleled the effects on K8 with respect to alterations in filament organization and solubility.…”
Section: K8 Is Phosphorylated On Conserved Rod Domain Residuementioning
confidence: 99%
“…66 Using different mouse models, the accumulation of RFs was shown to be caused by mutant GFAP protein and also by overexpression of wild-type human GFAP, suggesting that elevation of total levels of GFAP is a critical element. 67,68 All GFAP mutations discovered in AxD patients allow production of functional full-length mutant protein, 69 but mutant GFAP tends to form abnormally large, soluble oligomers, 70 and hence, progressive accumulation of mutant GFAP impacts protein metabolism in several ways. Astrocytes and RFs in AxD contain abundant amounts of chaperone proteins suggesting cell stress potentially through the accumulation of misfolded GFAP.…”
Section: Autophagy In Pediatric Brain Diseasesmentioning
confidence: 99%
“…As it has been reported that gigaxonin regulates GFAP in astrocytes 48 , quantifying the levels of GFAP in body fluids may be useful to determine the severity and/or clinical progression of GAN. Normally, low levels of GFAP are seen in body fluids, and will thus require the development of very sensitive detection methods, such as sandwich ELISA assays 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Normally, low levels of GFAP are seen in body fluids, and will thus require the development of very sensitive detection methods, such as sandwich ELISA assays 49 . CSF GFAP levels have been shown to be elevated in a number of neurological conditions, reflecting a wide range of etiologies (reviewed in 50 ). In several situations GFAP is evaluated relative to other biomarkers linked to neuronal damage, such as neurofilaments 51, 52 .…”
Section: Introductionmentioning
confidence: 99%